Quality of online video resources concerning patient education for neck pain: A YouTube-based quality-control study - Zhang, Xiang; Yang, Yi; Shen, Yi-Wei; Zhang, Ke-Rui; Ma, Li-Tai; Ding, Chen; Wang, Bei-Yu; Meng, Yang; Liu, Hao (Frontiers in Public Health, 2022)
Background: More than 70% of the global population suffers from neck pain at least once in their lifetime, of which 50% to 85% recur within 1 to 5 years of the initial episode. YouTube is increasingly being utilized as a source of health education about a variety of medical conditions. The study aimed to evaluate the quality and reliability of the information concerning neck pain shared on YouTube. Methods: A YouTube search was performed using the keyword “neck pain”, and the first 50 videos listed by relevance were included and categorized into seven and five groups based on their source and content. Each video included in the study was assessed using the Journal of American Medical Association (JAMA) score, DISCERN, Global Quality Score (GQS), Neck Pain Specific Score (NPSS), and video power index (VPI). Spearman correlation analysis was applied to assess the correlation between JAMA, GQS, DISCERN, NPSS, and VPI. A multiple linear regression analysis was performed to identify video characteristics affecting JAMA, GQS, DISCERN, and NPSS. Results: The videos had a mean JAMA score of 2.56 (SD=0.43), DISCERN of 2.55 (SD=0.44), GQS of 2.86 (SD=0.72), and NPSS of 2.90 (SD=2.23). On the basis of source, nonphysician videos had the greatest share at 38%, and based on content, exercise training comprised 40% of the videos. The VPI (P=0.012), JAMA (P<0.0001), DISCERN (P<0.0001), GQS (P=0.001), and NPSS (P=0.007) differed significantly among the six groups of video sources. JAMA, DISCERN, GQS, and NPSS were significantly correlated with each other (P<0.0001). Multiple linear regression analysis showed that a higher JAMA score, DISCERN, or GQS score was associated with a higher probability of an academic, physician, nonphysician or medical upload source (P<0.005), and a higher NPSS score was associated with a higher probability of an academic source (P=0.001). Conclusions: YouTube videos on neck pain have low quality and reliability. Patients may be put at risk for health complications due to inaccurate, and incomplete information, particularly during the COVID-19 crisis. Our findings suggest that academic groups should provide high-quality video content to YouTube users and patients.